Auroville, the city of Nature’s Yoga: material, spiritual and sustainable architecture and urbanism - Cunha, Pedro Henrique Azalim (National Journal of City Management, 2023)
This article aims to reflect on ongoing research that investigates cosmopolitical and spiritual practices in Auroville, an urban experience in southern India that emerged from the teachings of Sri Aurobindo (1872-1950), creator of Integral Yoga, philosopher, yogi, poet and icon of the nationalist struggle. This city adopts sustainable urban planning and architecture techniques that seek to be an example for the creation of a new human being integrated into the cosmos, living a collective life centered on the Yoga of Nature. Auroville aims to be "the city the world needs" and to inspire other cities towards sustainable practices, enabling a transformation in the world. The city center is a temple dedicated to concentration and meditation, but not linked to any religion. Ecological and spiritual practices act as guidelines for a more balanced and natural collective life, enabling an integration of material-spiritual architecture and urbanism with nature. The methodology used included in-depth interviews and participant observation during the field visit. The one-month experience in Auroville showed that, despite its many positive aspects, the contradictions inherent in such an experience are inevitable. The concentration of national and international resources, the recovery of the soil and forest, the solutions to guarantee drinking water supplies, roads, paths and infrastructure in general have changed the entire region. Spiritual tourism and commercial migration have contributed to a process of micro-regional real estate speculation. An internal conflict over the direction of the city and its surroundings, over the very integration of city-nature, is worrying Aurovillians today.